Comprehensive multiphase NMR: a promising technology to study plants in their native state. (9th April 2015) - Wheeler, Heather L.; Soong, Ronald; Courtier‐Murias, Denis; Botana, Adolfo; Fortier‐Mcgill, Blythe; Maas, Werner E.; Fey, Michael; Hutchins, Howard; Krishnamurthy, Sridevi; Kumar, Rajeev; Monette, Martine; Stronks, Henry J.; et al.
<x xml:space="preserve">Abstract</x> Nuclear magnetic resonance (NMR) spectroscopy is arguably one the most powerful tools to study the interactions and molecular structure within plants. Traditionally, however, NMR has developed as two separate fields, one dealing with liquids and the other dealing with solids. Plants in their native state contain components that are soluble, swollen, and true solids. Here, a new form of NMR spectroscopy, developed in 2012, termed comprehensive multiphase (CMP)‐NMR is applied for plant analysis. The technology composes all aspects of solution, gel, and solid‐state NMR into a single NMR probe such that all components in all phases in native unaltered samples can be studied and differentiated in situ. The technology is evaluated using wild‐type Arabidopsis thaliana and the cellulose‐deficient mutant ectopic lignification1 (eli1) as examples. Using CMP‐NMR to study intact samples eliminated the bias introduced by extraction methods and enabled the acquisition of a more complete structural and metabolic profile; thus, CMP‐NMR revealed molecular differences between wild type (WT) and eli1 that could be overlooked by conventional methods. Methanol, fatty acids and/or lipids, glutamine, phenylalanine, starch, and nucleic acids were more abundant in eli1 than in WT. Pentaglycine was present in A. thaliana seedlings and more abundant in eli1 than in WT. Copyright © 2015 John Wiley & Sons, Ltd.